Peran Aplikasi “Visiting Jogja” dalam Mengembalikan Kepercayaan Wisatawan untuk Berwisata ke Yogyakarta - Fitria Jalaluddin; Alfelia Nugky Permatasari (Jurnal Pariwisata Terapan, 2021)
Covid-19 made several countries adopt lock-down policies as an effort to break the chain of spreading the virus. However, this policy greatly affects sectors related to the daily mobility of people, especially the tourism sector which has been most significantly affected by Covid-19. One of the provinces in Indonesia that has experienced a major loss in the tourism sector due to Covid-19 is the Yogyakarta Special Region (DIY). Therefore, the DIY government gradually continues to encourage the tourism sector to resume operations, one of which is by releasing new applications for tourists, namely "Jogja Pass" and "Visiting Jogja" to monitor visitors to tourism destinations in DIY. In this study the author will focus on studying the application "Visiting Jogja". The purpose of this research is to examine the advantages and disadvantages of the "Visiting Jogja" application from the user's point of view, and to find out whether the "Visiting Jogja" application can help restore the confidence of tourists to travel to Yogyakarta. This study uses qualitative research methods, with data collection techniques through direct interviews with 10 respondents as a sample who is determined randomly. The results show that the application "Visiting Jogja" can provide assurance for tourists, which helps generate confidence in users to visit more tourism attractions in Yogyakarta. However, the government's efforts in socializing and promoting the “Visiting Jogja” application to the public are still lacking.